Does Value-Based Care Threaten Joint Arthroplasty Access for Vulnerable Patient Populations?: AOA Critical Issues. (2nd November 2022) - Lin, Eugenia; Bozic, Kevin J.; Ibrahim, Said; O'Connor, Mary I.; Nelson, Charles L.
Abstract: Health-care expenses have been projected to increase from 17.7% of the U.S. gross domestic product (GDP) in 2014 to 19.6% in 2024. The unsustainable increase in health-care costs has contributed toward support for value-based health care (VBHC) reform. Contemporary VBHC reform programs relevant to orthopaedic surgery include the voluntary Bundled Payments for Care Improvement initiatives (BPCI and BPCI-Advanced) and the Comprehensive Care for Joint Replacement (CJR) program, a mandatory bundled payment program. The purported benefits of transitioning from volume-based reimbursement to value-based reimbursement include moving from a fragmented provider-centered care model to a patient-centered model, with greater care coordination and alignment among providers focused on improving value. VBHC models allow innovative strategies to proactively invest resources to promote value (e.g., the use of nurse navigators) while eliminating unnecessary resources that do not promote value. However, major concerns regarding VBHC include the absence of medical and socioeconomic risk stratification as well as decreased access for higher-risk patients. This article identifies the benefits and potential unintended consequences of VBHC reform, with a focus on joint arthroplasty. We also discuss some potential strategies to promote innovation and improve value without compromising access for vulnerable patients.